Training individuals in suicide prevention: individual and organizational characteristics of effective gatekeepers - Moore, Jeffery Taylor, author; Harman, Jennifer J., advisor; Chen, Peter Y., advisor; Rosecrance, John C., committee member; Clegg, Benjamin A., committee member (Colorado State University. Libraries, 2011)
Suicide remains a major public health problem in the United States. Training individuals known as gatekeepers to identify the signs and behaviors of suicide risk has been one of the most widely adopted prevention strategies. Due to financial constraints, it is not possible to train all members of a community as gatekeepers. Thus, it is more fiscally responsible to selectively train individuals within a community who possess key characteristics that will make them more effective gatekeepers. In this dissertation, the personality and organizational characteristics of effective gatekeepers were explored. Specifically, personality characteristics: Emotional Intelligence and Altruism, and organizational characteristics: social support, perceived organizational support, and gatekeeper role conflict were investigated as predictors of gatekeeper behavior. Two hundred and eighteen gatekeepers completed surveys immediately prior, immediately after, and six months following training that consisted of self-report measures of personality and organizational characteristics, and gatekeeper behavior. Poisson regression was employed to analyze the data because of the low-base rate occurrence of gatekeeper behavior. Analyses were conducted separately for the two gatekeeper training programs (ASIST & QPR). Mixed results were found in this study. Gatekeepers trained in ASIST were high in Emotional Intelligence and Altruism, resulting in range restriction. Gatekeepers trained in QPR varied more on personality characteristics, and Altruism positively predicted gatekeeper behavior six months following training. In terms of organizational predictors of gatekeeper behavior, supervisor emotional support buffered the relationship between gatekeeper role conflict and gatekeeper behavior for ASIST participants. The findings have direct implications for the training of community members as gatekeepers. Specifically, how selection principles can be applied to gatekeeper training, as well as how social support can be improved in organizations so that gatekeepers can overcome barriers (such as role conflict) in order to increase the effectiveness of trained gatekeepers. Although a number of limitations were present in the current study (i.e., low response rate and inability to generalize the findings), the potential application of these findings presents the opportunity to significantly change who is selected for training as a gatekeeper and how trainings are conducted. Future research directions include the measurement of gatekeeper behavior and effectiveness of gatekeepers.
Keywords: gatekeeper; suicide; prevention; personality